Improving Consumers' Understanding and Use of Carbon Footprint Labels on Food: Proposal for a Climate Score Label - Dominic Lemken; Anke Zühlsdorf; Achim Spiller (EuroChoices, 2021)
Today, the food sector is largely excluded from climate protection policies. Nevertheless, the food sector is responsible for about 20 per cent of greenhouse gases. Food policies could substantially contribute to the EU's ambitious climate goals. Currently, the debate on CO2-e labelling is gaining momentum. Consumers know very little about the climate footprint associated with food choices. A climate label would strengthen consumer knowledge, may eventually influence food choices, could trigger reformulation efforts, raises awareness, and contribute to better informed discussions about climate policy. Based on a review of the current state of research and industry developments on designing CO2 footprint labels, this article provides recommendations on how to develop a clearly understood and trustworthy label. We propose a government approved, multi-level, and categorical CO2-e label, with colour coding and numeric CO2 equivalents; primarily based initially on median values. The design of the label should allow for an adoption of other environmental dimensions in the future. It should be scaled to weight (CO2-e per kg) and apply to food products and meals. In the proposed form, a CO2-e label is a low-cost instrument. As more and more companies are already starting to label their products in different ways, consumer confusion is likely to rise if no uniform guidelines are established.
Keywords: 630